1997
DOI: 10.1046/j.1365-2249.1997.d01-889.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and soluble IL-6 receptors (sIL-6R and sgp130) in human pleural effusions: massive IL-6 production independently of underlying diseases

Abstract: SUMMARYIL-6, soluble IL-6 receptor (sIL-6R) and soluble gp130 (sgp130) levels were measured in sera and pleural effusions from 42 patients with metastatic carcinoma, non-Hodgkin's lymphoma, tuberculosis, cardiac failure and miscellaneous diseases. Pleural IL-6 levels measured by ELISA were very high in all patient groups (mean 34 . 8 6 15 . 3 ng/ml) without significant difference according to diseases. IL-6 was shown to be biologically active in a proliferative assay. Serum IL-6 levels were low (0 . 049 6 0 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In contrast, the data obtained from different individual showed only a modest change, especially in CD, indicating that circulating levels of sgp130 should be evaluated individually in each patient. The measurement of serum sgp130 probably does not have a role in specific diagnosis because it is likely to be raised in other disease conditions [27]. Nevertheless, its serial measurement may help to determine disease prognosis and confirm treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the data obtained from different individual showed only a modest change, especially in CD, indicating that circulating levels of sgp130 should be evaluated individually in each patient. The measurement of serum sgp130 probably does not have a role in specific diagnosis because it is likely to be raised in other disease conditions [27]. Nevertheless, its serial measurement may help to determine disease prognosis and confirm treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, however, about the role of sgp130 in human diseases, including inflammatory conditions of the gastrointestinal system. One study has reported on the sgp130 levels in sera and pleural effusions from patients with metastatic carcinoma, non-Hodgkin's lymphoma, tuberculosis and cardiac failure [27].…”
Section: Introductionmentioning
confidence: 99%
“…Increased sIL‐6R levels in the peripheral blood have been demonstrated in various human diseases. 20–23 Recently, Mitsuyama et al demonstrated that serum sIL‐6R concentrations were raised in patients with active IBD. 24 However, little is known about intestinal sIL‐6R levels in patients with IBD and what cell types are involved in sIL‐6R secretion in the intestinal mucosal lesions of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…From each patient, depending on body weight, we collected 0.1-1.0 mL of peripheral blood at up to 10 different time points. We also obtained postoperative drainage fluids from the pericardium or the pleura from five of the patients as high IL-6 concentration samples (7 ). A total of 187 samples were collected and centrifuged at 2500g for 10 min; the supernatants were collected and stored in aliquots at Ϫ80°C until analysis.…”
mentioning
confidence: 99%